A Norbert for England: Holy Trinity and the Invention of Robert of Knaresborough - Easterling, Joshua (Journal of Medieval Monastic Studies, 2013)
This essay considers the relationship between two monastic vitae and their historical subjects. The prose vita of the English hermit Robert of Knaresborough that is extant in London, British Library, MS Egerton 3143 contains a number of passages borrowed from the Vita B of Norbert of Xanten, the founder of Premontre. These two otherwise unaffiliated figures of religious reform are connected through Robert’s biographer, most likely a brother of the late-established Trinitarian Order, who extracted key details from Norbert’s vita to shape Robert in the founder’s image. In Egerton’s prose vita, Robert is ultimately made to serve as a legitimate origin for, and as a founder of, the Trinitarian Order at Knaresborough.
Publisher: Brepols Publishers
Keywords: 👤 norbert of xanten

A 14th-Century Sculpted Arcade from Coverham Abbey - Harrison, Stuart A. (Journal of the British Archaeological Association, 2013)
Keywords: coverham

Looking Anew at the curvilinear tracery of the Bellapais Abbey Cloister - Olympios, Michalis (Cahiers du Centre d'Études Chypriotes, 2013)
Keywords: bellapais

The Bolton Scropes and Easby Abbey: a family mausoleum in context - Werronen, Stephen (Bulletin of international medieval research, 2013)
Keywords: easby

Human remains from the cloister garth of the 'Koningsveld' priory near the medieval city of Delft, ca. 1450-1572AD - Westen, A.A.; Groen, W.J.; Maat, G.J.R. (Stichting ter Financiering van Barge’s Anthropologica, 2013)
Keywords: delft